Interferon type I signature associated with skin disease in juvenile dermatomyositis - Raupov, Rinat; Suspitsin, Evgeny; Preobrazhenskaya, Elena V.; Kostik, Mikhail (Frontiers in Medicine, 2024)
Background: Interferon type I (IFN-I) signaling system hyperactivation plays an important role in the pathogenesis of juvenile dermatomyositis (JDM).: to analyze IFN-I score with disease activity in patients with JDM Materials and methods: clinical manifestations laboratory data, and treatment options were analyzed in 15 children with JDM. Disease activity was assessed by CMAS (childhood myositis assessment tool) and CAT (cutaneous assessment tool) scores. IFN I-score was assessed by RT-PCR quantitation of 5 IFN I-regulated transcripts (IFI44L, IFI44, IFIT3, LY6E, MXA1).Results: All patients had skin and muscle involvement, some had a fever (n=8), swallowing disorders (n=4), arthritis (n=5), calcinosis (n=3), lipodystrophy (n=2), and interstitial lung disease (n=5). Twelve patients had elevated IFN I-score and it was correlated with skin disease activity. Ten patients had clinically active disease and the level of IFN I-score and its components were higher than in patients with inactive disease (8.8 vs 4.2, p= 0.011). IFN I-score was evaluated in nine patients during follow-up. The simultaneous reduction of IFN I-score and its components, CMAS and CAT scores was observed.Skin involvement in refractory JDM is a challenging problem requiring the use of additional medications. Serum IFN I-score might be suggested as the promising biomarker of skin disease activity in JDM patients. Further investigations on patients with JDM and recurrent disease activity are needed, especially concerning biomarkers that determine the response to JAK inhibitors and treatment options for patients who don't respond to them.